Defining the problem of low wage growth in Australia and Denmark: From the actors' perspectives. (June 2023) - Andersen, Søren Kaj; Wright, Chris F; Lansbury, Russell D
Low wage growth is a challenge common to many OECD countries including countries with very different institutional systems. This paper utilises and extends Rochefort and Cobb's (1993) 'problem definition' framework to analyse how employer and union representatives in Australia and Denmark explain the causes of low wage growth. Drawing on elite interviews, which allow us to assess the nuance of actors' perceptions, we find disagreement among Australian actors about the role of the collective bargaining system in contributing to low wage growth. Despite disagreement over the extent of the low wage growth problem in Denmark, both unions and employers expressed confidence in the ability of the bargaining system to resolve it. We argue that the greater degree of consensus in Denmark compared with Australia reflects differences in national institutional systems and knowledge regimes, which have influenced the ways actors in these countries perceive low wage growth.